Renaissance and Reformation : - Green, V. H. H. (St. Martin's Press, 1964)
The period of history under consideration is of such momentous importance, and so full of detail that the historian may well be baffled by the difficulty of selecting what is really relevant to his purpose. But I have essayed to write a book which can serve the dual purpose of informing a general reader of what happened in Europe in the sixteenth and early seventeenth centuries and of placing a text at the disposal of the history specialist in a school or the undergraduate at a university.